Gender Perspective in Migration: Reflections on the Role of Institutions - Mena Gómez, Sileny (2025)
The article examines social representations and institutional practices related to the gender perspective in addressing migrant populations. The study was conducted between 2022 and 2024 and employed a qualitative methodology incorporating gender and intersectional perspectives. The findings reveal that integrating this approach into institutional work enables the identification of specific vulnerabilities based on migratory status, gender, and other structural inequalities.